Retrospektivna analiza padova kod obolelih od plućnih bolesti u hospitalnim uslovima: Falls in hospitalized pulmonary patients - Vojnović, Jelena; Hromiš, Sanja; Novković Joldić, Mira; Brestovački Svitlica, Branislava; Obrenov, Ljubica (PONS - medicinski časopis, 2025)
OBJECTIVE: Patient falls are categorized as the most common adverse events in hospital practice. Lung patients are elderly, multimorbidity, limited mobility and cognitive dysfunctions, which is why they may have an increased risk. The aim of this research is to analyze the risk factors of falls during hospitalization of patients with lung diseases, as well as their causes and consequences. METHOD: The study was designed as a retrospective - a pilot study on a sample of 37 patients with lung diseases, both sexes, aged from 43 to 90 years. Data were collected from medical records. The results are presented tabularly and graphically.RESULTS: The sample consisted of 51% male and 49% female respondents, 92% aged >60 years. Analysis of risk factors indicated the greatest degree of increased risk of falling: older age > 60 years 92%, respiratory insufficiency 89%, multimorbidity 97%, drugs with risk factors 97% and additional equipment 97%. The main causes of falls in 68% of patients are cognitive dysfunction, in 19% environmental factors, while in 13% the cause of the fall is unknown. In our sample, 54% of the respondents were without injuries.CONCLUSION: Based on this pilot study, we can conclude that there are a lot of associated risk factors that contribute to increased risk of falling in the studied population group, and in future research it is necessary to examine them in more detail in other lung diseases, not only in patients with COPD.KEYWORDS:  falls, risk factors, assesment risk